Anti-Inflammatory and Anticancer Effects of Anthocyanins in In Vitro and In Vivo Studies - Tomasz Kowalczyk; Martyna Muskała; Anna Merecz-Sadowska; Joanna Sikora; Laurent Picot; Przemysław Sitarek (MDPI AG, 2024)
Anthocyanins, a class of flavonoid compounds responsible for the vibrant colors of many fruits and vegetables, have received considerable attention in recent years due to their potential health benefits. This review, focusing on evidence from both in vitro and in vivo studies, provides a comprehensive overview of the current state of knowledge regarding the health-promoting properties of anthocyanins. The chemical structure and diversity of anthocyanins, their bioavailability, and their mechanisms of action at the cellular and molecular level are examined. Research on the antioxidant, anti-inflammatory, anticancer, and neuroprotective effects of anthocyanins is critically reviewed. Special emphasis is placed on the role of anthocyanins in the prevention and treatment of chronic diseases such as cardiovascular diseases, diabetes, and neurodegenerative diseases. This review also discusses the challenges of translating in vitro findings to in vivo and highlights the importance of considering dose, bioavailability, and metabolism when assessing the therapeutic potential of anthocyanins. This review concludes with the identification of gaps in current research and suggestions for future directions for anthocyanin studies, including the need for more long-term clinical trials and investigations into potential synergistic effects with other phytochemicals. This comprehensive analysis highlights the promising role of anthocyanins in promoting human health and provides valuable insights for researchers, health professionals, and the nutraceutical industry. This study provides new insights, as it comprehensively investigates the dual anti-inflammatory and anticancer effects of anthocyanins in both in vitro and in vivo models. By uncovering the biological properties of anthocyanins from a variety of natural sources, this research not only expands our knowledge of the action of these compounds at the cellular level, but also enhances their clinical relevance through in vivo validation. Furthermore, the innovative use of anthocyanins may lead to important advances in their therapeutic application in the future.